2016
DOI: 10.1002/ajh.24270
|View full text |Cite
|
Sign up to set email alerts
|

Impact of age on outcomes of allogeneic hematopoietic stem cell transplantation with reduced intensity conditioning in elderly patients with acute myeloid leukemia

Abstract: Previous studies have repeatedly reported that increasing age is a significant risk factor for worse outcomes after allogeneic hematopoietic stem cell transplantation (allo-HSCT) among patients with acute myeloid leukemia (AML). However, more recent studies reported conflicting results regarding the association between age and outcomes in elderly patients. Therefore, we conducted a large-scale, nationwide retrospective study to examine the impact of age on outcomes of allo-HSCT with reduced intensity condition… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

5
23
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(29 citation statements)
references
References 23 publications
5
23
0
1
Order By: Relevance
“…Compared to other published data in similar patient population, our results show comparable survival and disease control rates [3-6, [22][23][24]. For example, a recent study of 187 patients with AML and MDS by Pohlen et al…”
Section: Discussionsupporting
confidence: 78%
“…Compared to other published data in similar patient population, our results show comparable survival and disease control rates [3-6, [22][23][24]. For example, a recent study of 187 patients with AML and MDS by Pohlen et al…”
Section: Discussionsupporting
confidence: 78%
“…Older patients less often have HLA-matched related donors. Additionally, they have increased post-transplantation mortality caused by severe graft-versus-host disease (GVHD) [4][5][6]. To overcome this barrier, HLA-mismatched cellular therapy (stem cell [SC] microtransplantation [MST]) after conventional chemotherapy was developed to improve complete remission (CR) and OS and to reduce regimen-related toxicity compared to conventional chemotherapy [7].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, comprehensive geriatric assessment is currently under investigation in assessing patients' vulnerabilities before HSCT and could be a useful tool to select those patients more likely to benefit from the transplant procedure. Regarding transplant efficacy, Aoki et al reported encouraging disease-free and overall survival rates for selected patients older than 65 years, suggesting that age alone had no significant impact on transplant outcome [40]. Similarly, Kurosawa et al, in a registry survey of adults aged 50-70 years, in first complete remission (CR1), showed a longer 3-year OS for those who received HSCT rather than chemotherapy alone (62% vs. 51%, respectively), confirming a survival advantage of the transplant procedure, especially in high-risk patients [41].…”
Section: Allogeneic Hematopoietic Stem Cell Transplantationmentioning
confidence: 99%